EFFECT OF VITAMINS, HONEY AND TEMULAWAK ON THE APPETITE IMPROVEMENT OF CHILDREN AGE 2 YEARS IN SEMBUNG SUKORAME LAMONGAN - UTAMI, WORO TRI; KURNIA HELI, ANITA SRI (Asuhan Kesehatan : Jurnal Ilmiah Ilmu Kebidanan dan Keperawatan, 2015)
ABSTRACTToddlers group belong to the vulnerable group of nutrition, often in Toddlers disorder or problem difficult to eat. Difficult child eat should immediately get attention because if this situation lasts longer will result in growth disorders.This research is descriptive and exploratory research, with a total sample of 30 children were divided into 3 groups: 10 children were given vitamin, 10 toddlers and 10 toddlers were given honey given buffoonery. This research was conducted in July to August 2014 Sembung Sukorame Lamongan.The results showed vitamin, honey and ginger effect on weight gain, but of the three most influential treatments are given vitamin indicated by ANOVA with a significant level ? = 0:05 is 0.000 (0.122), and ginger 0:10 (0122). Variable diet to increase appetite shows the value of F is 16 558 and F0.05 is 3:35 so Fhitung> F0.05 means the provision of vitamins, honey and ginger effect to increase appetite toddler. The test results statistic variable drinking patterns against an increase in appetite show F hit use values are 4934 and F0.05 is 3:35 so Fhitung> F0.05 means the provision of vitamins, honey and ginger effect on drinking patterns to increased appetite toddler. ANOVA statistical test result variable pattern of activity to increased appetite shows F hit value is 0.364 and F0.05 is 3:35 so Fhitung <F0.05 means the provision of vitamins, honey and ginger has no effect on the activity of the increased appetite toddler.   Keywords: Vitamins, Honey, Ginger, Appetite, Toddler Age 2 Years